2017
DOI: 10.3390/w9110829
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Microbial Community in an Anammox Process Using Stored Anammox Sludge

Abstract: This study investigated a rapid start-up anaerobic ammonium oxidation (Anammox) process by inoculation with stored Anammox sludge and characterized the associated microbial communities. The Anammox process took only 43 days to start. A high nitrogen removal rate of 1.13 kg N m −3 d −1 and a nitrogen loading rate of 1.28 kg N m −3 d −1 were achieved. The ratio of ammonium removal to nitrite removal to nitrate production (1:1:0.2) was slightly lower than the theoretical value, which indicated nitrogen removal by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…We focused the analysis of recovered MAGs on the genomic properties of high abundance populations that differed in abundance between reactor configurations to develop hypotheses of how the selective pressures imposed by the distinct reactor configurations may impact the microbial community structures and their potential functions. Previous studies of PNA bioreactors have observed microbial community structures over time, with some stability observed in bench scale reactors ( Chen et al, 2017 ) and conversely, community dynamics have been observed that correlated with changes in influent ammonia and nitrite concentrations ( Huang Q. et al, 2018 ). The community structure and potential function of PNA granules is also impacted by granule size, with nitrifiers being more abundant in smaller granules and larger granules harboring greater species diversity ( Luo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We focused the analysis of recovered MAGs on the genomic properties of high abundance populations that differed in abundance between reactor configurations to develop hypotheses of how the selective pressures imposed by the distinct reactor configurations may impact the microbial community structures and their potential functions. Previous studies of PNA bioreactors have observed microbial community structures over time, with some stability observed in bench scale reactors ( Chen et al, 2017 ) and conversely, community dynamics have been observed that correlated with changes in influent ammonia and nitrite concentrations ( Huang Q. et al, 2018 ). The community structure and potential function of PNA granules is also impacted by granule size, with nitrifiers being more abundant in smaller granules and larger granules harboring greater species diversity ( Luo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%